Cognitive performance and morning levels of salivary cortisol and α-Amylase in children reporting high vs. low daily stress perception - Maldonado, Enrique F.; Fernandez, Francisco J.; Trianes, M. Victoria; Wesnes, Keith; Petrini, Orlando; Zangara, Andrea; Enguix, Alfredo; Ambrosetti, Lara (The Spanish Journal of Psychology, 2008)
The aim of the present study was to assess the effects of daily stress perception on cognitive performance and morning basal salivary cortisol and alpha-amylase levels in healthy children aged 9-12. Participants were classified by whether they had low daily perceived stress (LPS, n = 27) or a high daily perceived stress (HPS, n = 26) using the Children Daily Stress Inventory (CDSI). Salivary cortisol and alpha-amylase were measured at awakening and 30 minutes later. Cognitive performance was assessed using the Cognitive Drug Research assessment system. The HPS group exhibited significantly poorer scores on speed of memory (p < .05) and continuity of attention (p < .05) relative to the LPS group. The HPS group also showed significantly lower morning cortisol levels at awakening and at +30 minutes measures in comparison with the LPS group (p < .05), and mean morning cortisol levels were negatively correlated with speed of memory (p < .05) in the 53 participants. No significant differences were observed between both groups in alpha-amylase levels. These findings suggest that daily perceived stress in children may impoverish cognitive performance via its modulating effects on the HPA axis activity.